2015
DOI: 10.1016/j.actbio.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell mechanics – An experimental–computational method for quantifying the membrane–cytoskeleton elasticity of cells

Abstract: This is the first study to decouple the membrane-cytoskeleton elasticity from cell stiffness and introduce an effective approach for measuring the elastic modulus. The novelty of this study is the development of new technology for quantifying the elastic stiffness of the membrane-cytoskeleton system of cells. This capability could have immense implications in cell biology, particularly in establishing correlations between various cell diseases, mortality, and differentiation with membrane-cytoskeleton elastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This nanomechanical phenotype is a complex result of the unique properties of cell membrane, underlying cytoskeleton and cell turgor, which together reflect an epithelial-mesenchymal transition for promoting cell mobility (34). Nanomechanical parameters, most notably elasticity and adhesion, have been proposed to provide a rich resource for robust characterization of human cells, including distinguishing between cancer and normal cells, and also for fine stratification of cancer cells according to their malignancy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…This nanomechanical phenotype is a complex result of the unique properties of cell membrane, underlying cytoskeleton and cell turgor, which together reflect an epithelial-mesenchymal transition for promoting cell mobility (34). Nanomechanical parameters, most notably elasticity and adhesion, have been proposed to provide a rich resource for robust characterization of human cells, including distinguishing between cancer and normal cells, and also for fine stratification of cancer cells according to their malignancy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional platforms can be easily combined with techniques such as atomic force microscopy (AFM) (as an example) to not only measure the mechanical properties of migrating cells but also assess the cellular response to cellular and matrix deformations that are created using the AFM cantilever [93]. In metastasis research, AFM has been utilized in conjunction with 2D models of migration to study the mechanical properties of migrating cells by investigating and characterizing alterations to the cytoskeleton and ECM [94][95][96][97][98]. Such studies have demonstrated that the cytoskeleton of metastatic cells responds to mechanical loads differently than that of a nonmetastatic cell, as these cells are typically more compliant [99,100].…”
Section: Two-dimensional Versus 3d Metastatic Movementmentioning
confidence: 99%
“…Conventional techniques such as micropipette aspiration 21 , optical tweezer 22 , and atomic force microscopy (AFM) 23,24 apply localized forces to single cells to characterize cellular mechanical properties. However, these techniques are generally not amenable for assessing an ensemble of cells simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, AFM has been utilized to assess mechanical property of cells 24,32 including macrophages 20,33,34 . Used as an indentation method via the compression of cantilever onto the cell membrane and measurement of ensuing deformation of the cell surface, Young’s modulus of macrophages were obtained to be in a wide range of values 20,33,34 , from 0.8 kPa up to 60 kPa, depending on factors such as surface coating and incubation time.…”
Section: Discussionmentioning
confidence: 99%